Respuesta :

Part 1: Answer:

(x+1)(x+1)(x-6) = x^3 - 4x^2 - 11x - 6

Step-by-step explanation:

To make r a root, include (x-r) as a factor. (-1+1)(-1+1)(-1-6) is zero even though (-1-6) isn't.

(6+1)(6+1)(6-6) is zero.


Part 2 Answer:

Standard form: y = -x^4 + 12

Degree 4

left end goes down, right end goes down.

Step by step: apply the definitions of standard form, polynomial degree, and "end behavior". In other words, read the textbook.


Part 3: Answer: x = 3, x = 8

Step by step:

x^2-11x = -24

x^2-11x+24 = 0

(x-3)(x-8) = 0

x = 3 or x = 8


Part 4a Answer:

quotient 2x^2 + x - 3

remainder 1


Step by step:

2x^2 + x - 3

___________________

x-4 ) 2x^3 - 7x^2 - 7x + 13

2x^3 - 8x^2

__________

0 + x^2 - 7x + 13

x^2 - 4x

____________

0 - 3x + 13

- 3x + 12

______

1


Part 4b answer:

quotient 2x^2 - 6x + 2

remainder -20


Step by step: you have to know exactly what you are doing. Refer to textbook or Wikipedia.


dividend 2x^3 +14x^2 - 58x

divisor x+10

leading coefficient of divisor must be 1

write coefficients of dividend at top

write coefficients of dividend at left


| 2 14 -58 0

-10 | -20 60 -20

___________

| 2 -6 2 -20

Coefficients of quotient are 2 -6 2

Remainder is -20

quotient = 2x^2 - 6x + 2



ACCESS MORE